2007
DOI: 10.1097/hjr.0b013e32804955b3
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and myocardial infarction case-fatality: hospital and population approach

Abstract: Background Smoking is a risk factor for coronary heart disease, but it has been associated with better short-term prognosis in hospitalized patients with acute myocardial infarction. The aims of this study were to determine the association between smoking and myocardial infarction 28-day case-fatality in hospitalized patients and at the population level; and, whether smokers presenting with fatal myocardial infarction are more likely to die before reaching a hospital. Design and methods Population-based myocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…The 'smoker's paradox' observed in our study has been well described in previous studies of myocardial infarctions [28][29][30] , but was not observed in a large stroke outcome study conducted in China [31] . The Copenhagen Stroke Study found a protective effect of smoking on 5-year survival in univariate analyses, but a 20% excess after multivariate adjustment [32] .…”
Section: Discussionsupporting
confidence: 87%
“…The 'smoker's paradox' observed in our study has been well described in previous studies of myocardial infarctions [28][29][30] , but was not observed in a large stroke outcome study conducted in China [31] . The Copenhagen Stroke Study found a protective effect of smoking on 5-year survival in univariate analyses, but a 20% excess after multivariate adjustment [32] .…”
Section: Discussionsupporting
confidence: 87%
“…Four observational studies did not adjust for any treatment provided during hospitalisation [14,16,25,26]. Three registries [15,17,19], in addition to the CADILLAC trial [27], included invasive treatment in the multivariate analyses. The NRMI 2 registry adjusted for "any reperfusion therapy" without specifying the proportion of patients undergoing invasive procedures [18].…”
Section: Resultsmentioning
confidence: 99%
“…One of these studies was an observational single-centre study enrolling unselected AMI patients between 1982 and 1984 [25]. The five other studies dated from the late 1980s and early 1990s and included patients according to the former WHO classification and before the routine use of invasive revascularisation [12,13,15,18,26]. …”
Section: Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported lower mortality after acute myocardial infarction in smokers [17][18][19] . Smoking is a well-known risk factor for vascular diseases and mortality; therefore our paradoxical findings might be explained by differences in the distribution of other risk factors for stroke mortality, and by differences in comorbidity between smokers and non-smokers.…”
Section: Discussionmentioning
confidence: 99%